HIGHER BMI, HIGHER RISK? INVESTIGATING THE LINK BETWEEN OBESITY AND CHOLELITHIASIS ACROSS ASIA: A SYSTEMATIC REVIEW - Ario Achwanu Shafa; Bambang Arianto (The International Journal of Medical Science and Health Research, 2025)
Background: Cholelithiasis represents a significant global health burden, with obesity as a major modifiable risk factor. Yet systematic reviews examining BMI-cholelithiasis relationships using WHO-recommended Asian-specific cutoffs (overweight ≥23 kg/m², obese ≥25 kg/m²) remain scarce. This review investigates how elevated BMI relates to cholelithiasis across Asian populations when appropriate thresholds are applied. Methods: Following PRISMA 2020 guidelines, we searched PubMed, Scopus, and Cochrane Library (January 2015-December 2025). Two reviewers independently screened studies using Rayyan.ai and predefined PICOS criteria, with a critical requirement: explicit use of Asian-specific WHO BMI cutoffs. We extracted demographics, BMI-stratified outcomes, and effect estimates, then assessed quality using Newcastle-Ottawa Scale. Results: Of 366 studies screened, only four met inclusion criteria—spanning Korea, Taiwan, China, and Indonesia with sample sizes from 124 to over 724,000 participants. All four demonstrated consistent BMI-cholelithiasis associations: effect sizes ranged from modest (OR 1.5-2.0) to substantial (OR >5.0) for high-risk groups. We identified a dose-response relationship of 4.2% increased odds per 1 kg/m² BMI increment. Metabolically abnormal obese individuals under 50 years faced particularly dramatic risk (OR 5.41). Female sex, younger age, and specific ethnicities further amplified susceptibility. Conclusion: Elevated BMI strongly predicts cholelithiasis when Asian-appropriate thresholds are used. The consistent dose-response relationship and amplified risk in metabolically abnormal individuals demand urgent action. Researchers, clinicians, and policymakers must adopt Asian-specific BMI thresholds to generate and implement effective prevention strategies across Asia's diverse populations.